2020
DOI: 10.1093/jpepsy/jsaa015
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation for Children with Chronic Conditions: A Systematic Review and Meta-analysis

Abstract: Objective This systematic review and meta-analysis evaluated the effectiveness of psychoeducational interventions in improving quality of life (QoL) for children with chronic conditions. Methods We identified 25 randomized controlled trials of psychoeducational interventions for children with chronic conditions that reported a QoL outcome and were published 1980–2018. Due to small numbers of interventions in other chronic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Psychoeducation refers to providing education around the patient's condition, teaching the skills required to manage illness, navigating relationships, and providing coping strategies 37 . Although we did not specifically evaluate the impact of psychoeducation in adolescents with cSLE, one study in children with other chronic illnesses, including diabetes and asthma, showed an improvement in quality‐of‐life measures 38 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Psychoeducation refers to providing education around the patient's condition, teaching the skills required to manage illness, navigating relationships, and providing coping strategies 37 . Although we did not specifically evaluate the impact of psychoeducation in adolescents with cSLE, one study in children with other chronic illnesses, including diabetes and asthma, showed an improvement in quality‐of‐life measures 38 …”
Section: Discussionmentioning
confidence: 98%
“…37 Although we did not specifically evaluate the impact of psychoeducation in adolescents with cSLE, one study in children with other chronic illnesses, including diabetes and asthma, showed an improvement in quality-of-life measures. 38 Reproductive health screening and counseling is ideally part of routine primary care, although time constraints and difficulty with access makes this limited in practice for many providers. 39 Additionally, youth with cSLE have been found to visit their rheumatologist more frequently than their primary care provider, 1 which places the onus on us to discuss these adolescent-specific issues.…”
Section: Discussionmentioning
confidence: 99%
“…Psychoeducational interventions have been shown to improve quality of life for patients with cancer (Barsevick et al, 2002). They are also effective at improving quality of life for children with asthma (Day et al, 2020). In addition, brief psychoeducation of any form has also been shown to reduce relapse and increase medication adherence across a range of mental health disorders in adults (Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%